OPTIMIZATION OF TREATMENT STRATEGIES FOR ACUTE CORONARY SYNDROME PATIENTS WITH ARRHYTHMIC COMPLICATIONS - Malikova Dildora Maxsud qizi; Sharopova Nargiza Samiyevna (TADQIQOTLAR, 2025)
Abstract. The presence of acute heart failure in patients with myocardial infarction remains one of the current problems in cardiology. The urgency of the problem is determined by the frequency of complications resulting from this pathology and the lack of a sufficiently effective treatment.